Sistem Pendukung Keputusan Pemilihan Anggota Terbaik Pemadam Kebakaran Dengan Menggunakan Metode Analitycal Hierarchy Proses (AHP) - Reva Gunawan (JURIKOM (Jurnal Riset Komputer), 2019)
Fire is a threat to human safety, property and the environment. Increasingly dense population, the construction of office buildings, residential areas, industries that are increasingly developing causing vulnerability in the event of a fire that requires special handling. The fire brigade or BPBD (Regional Disaster Management Agency) is a government implementing element that is given responsibility in carrying out the tasks of handling fire and disaster problems which are included in the emergency department or Rescue (Rescuers) such as Ambulance and the National SAR Agency. AHP (Analitycal Hierarchy Process) is a method for solving an unstructured complex situation into several components in a hierarchical arrangement, by giving a subjective value of the relative importance of each variable, and determining which variable has the highest priority to influence the outcome of the situation . The decision making process is basically choosing the best alternative. Such as structuring the problem, determining alternatives, determining the likelihood value for the aleatori variable, setting the value, the preference requirements over time, and the specification of risk. The results of the study show that the use of AHP as a model of decision support systems for selecting the Best Members of the Fire Department can help the admin in determining the Best Member with a multi-criteria weighting process and selection more quickly, accurately and more effectively.